Ileocecal valve atresia: Introduction of a new surgical approach - Seyed Abdollah Mousavi; Leila Sarparast (Wolters Kluwer Medknow Publications, 2014)
Ileocecal valve atresia is a very rare anomaly with only a few cases reported in the literature. The conventional therapy includes ileocecal resection and ileocolic anastomosis. Here, we present a patient with inborn ileocecal valve atresia in whom we successfully preserved the ileocecal valve and the terminal ileum through opening a valve and tapering the ileum in one operation.